LOCAL WISDOM VALUES OF THE MASTERPIECE OF RAJA ALI HAJI‘S “GURINDAM 12” - Gaguk Rudianto; Zakrimal (IdeBahasa, 2020)
Local wisdom is customs or culture of a society that contain noble values which are inherited from generation to generation which have been applied in the order to the community can protect and manage the environment sustainably. It contains moral teachings that have grown and developed in society from generation to generation and it is also the implementation of cultural values adopted by the community in managing natural resources to benefit life. Based on Vitasurya (2018), the function of local wisdom toward the entry of foreign cultures according as follows (1) As a filter and controlling the external culture. (2) Accommodating outside cultural elements (3) Integrate outside cultural elements into indigenous culture and (4) Give direction to cultural development. This research discussed about local wisdom which contained in the Master piece of Raja Ali Haji’s Gurindam 12 which started to dim away in the society because of unbearable information and technology development. Method of collecting data applied in this research was documentation where it was taken from both printed and electronic data. Method of analyzing data in this research was categorization proposed by Klepper et al (2017). The result of the research showed that Gurindam 12 contained about moral teaching relates to Islam religion in every stanza.